STUDY ON THE UTILIZATION OF WASTE AND WASTE CONSTRUCTION MATERIAL WITH THE CONCEPT OF REUSE & RECYCLE AS ARCHITECTURAL ELEMENTS - Fitriansyah Fitriansyah; M Syauqi Hikam Fayazid; Ismail Ismail; Hanif Budiman; Putu ayu Pramanasari Agustiananda (Architecture Department, Faculty of Engineering, Universitas Diponegoro, 2026)
Sustainability issues are present as a result of construction development, one of which is a contributor to carbon emissions. This study aims to explore the types of waste and specifically analyze the processing methods of used building materials and plastic waste to determine their suitability as architectural elements. This study uses a deductive qualitative method, which is a field data analysis approach using the Hierarchical Recycling theory to conclude the findings. Observations were conducted on two primary subjects: the application of construction demolition waste at Bocor Alus Cafe and the plastic recycling process at Paste Lab. The results identify a clear distinction in processing: construction waste, such as doors and windows, is most effective through Component Reuse which requires minimal energy, while plastic waste requires specific Recycling stages such as shredding and melting to become functional architectural components. The study concludes that applying these concepts not only reduces waste but also aligns with Islamic principles of environmental preservation and sustainability.